Polymorphism of Vitamin D Receptor Gene Taq1 (rs731236) and its Effect on Bone Turnover Markers in Iraqi Postmenopausal Osteoporotic Women After Vitamin D Supplementation - Noor Mohammed Abdulrahman; Shatha Hussein Ali (Iraqi Journal of Pharmaceutical Sciences, 2025)
There are many causes of osteoporosis, and one of them is deficiency in vitamin D resulting from vitamin D receptor polymorphism. This polymorphism makes the bones and tissues that contain vitamin D receptors resistant to vitamin D and not getting enough concentrations. The aim of this study is to find the correlation between vitamin D receptor Taq1 (rs731236) gene polymorphism and bone turnover markers (procollagen-I and deoxypyridinoline) in postmenopausal osteoporotic women after taking a certain dose of vitamin D. Forty postmenopausal women were included who were diagnosed with osteoporosis according to WHO guidelines by taking bone mineral density measurements by DXA-scan. The participating patients received a vitamin D dose (50000 IU/week) for a duration of two months; this is the patients’ group. The control group consisted of thirty postmenopausal women without osteoporosis. The patients were divided into two groups based on their responses to vitamin D doses. Regarding allele frequency, GA has a higher percent (57.5%, 46.6%) in the patients’ group and control group, respectively. There is a non-significant difference (p = 0.11) between responders, non-responders, or the control group regarding GA genotype frequency. Bone turnover markers (procollagen-I and deoxypyridinoline) show no significant difference between groups. (p=0.22, p=0.89) at the pre-treatment level, respectively. There is a significant difference (p = 0.01) in vitamin D levels between the patients’ group and the control group. Vitamin D receptor Taq 1 (rs731236) gene polymorphism can assist in osteoporotic development through its effect on vitamin D level and, as a sequence, on bone turnover markers, making female osteoporotic patients.